Federalism, secession, and the American state : divided, we secede - Anderson, Lawrence M. (Routledge studies in North American politics, 2013)
One important tradition in political science conceives of the Civil War in the United States serving as the functional equivalent of the English and French Revolutions, bringing with it the victory of liberal democratic industrialism over aristocratic agriculturalism. From this perspective, the Civil War is notable for its impact on the American state. Surprisingly however, little attention has been paid to the distinguishing features of this historic rupture in American politics. Through primary source research and the re-analysis of the rich historical literature about the an.